2018
DOI: 10.5194/bg-2018-51
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Riverine carbon export in the arid-semiarid Wuding River catchment on the Chinese Loess Plateau

Abstract: Riverine export of terrestrially-derived carbon represent a key component of the global carbon cycle. In this study we quantify the redistribution of riverine carbon within the 15Wuding catchment on the Chinese Loess Plateau. Export of dissolved organic and inorganic carbon (DOC and DIC) exhibited pronounced spatial and temporal variability. While the DOC concentration was spatially comparable within the catchment, it was generally higher in spring and summer than in autumn, especially in the loess subcatchmen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 51 publications
(85 reference statements)
1
12
0
Order By: Relevance
“…Preferential outgassing of 12 CO 2 may also have contributed to the more depleted δ 13 C values in the emitted CO 2 than that of the C 4 plants. Aquatic algae with their δ 13 C value ranging from −40 to −26 ‰ (Alin et al, 2008) is likely another contributor, as suggested by the 2-fold higher Chl a contents in summer and autumn than in spring at some sites (Ran et al, 2017). Deeply incised stream channels provide favorable stagnant water, albeit highly site specific, for algae growth during non-flooding periods.…”
Section: Carbon Isotopic Signature In the Emitted Comentioning
confidence: 98%
See 2 more Smart Citations
“…Preferential outgassing of 12 CO 2 may also have contributed to the more depleted δ 13 C values in the emitted CO 2 than that of the C 4 plants. Aquatic algae with their δ 13 C value ranging from −40 to −26 ‰ (Alin et al, 2008) is likely another contributor, as suggested by the 2-fold higher Chl a contents in summer and autumn than in spring at some sites (Ran et al, 2017). Deeply incised stream channels provide favorable stagnant water, albeit highly site specific, for algae growth during non-flooding periods.…”
Section: Carbon Isotopic Signature In the Emitted Comentioning
confidence: 98%
“…While detailed information has been provided in Ran et al (2017), a brief description is provided here. Three sampling campaigns were conducted in the Wuding River catchment in 2015: before the wet season (March-April; denoted as spring), during the wet season (July-August; sum- Figure 1.…”
Section: Field Sampling and Laboratory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Fluvial C is primarily of terrestrial origin and its transport in stream networks is closely linked to watershed hydrology. Heavy storm events typically promote the flushing of C‐rich soils leading to high DOC and POC fluxes, whereas the predominance of groundwater sources during baseflow contributes to high DIC flux in streamflow (Ran et al., 2018; Roebuck et al., 2018; Yoon & Raymond, 2012). The decrease in DOC and DIC concentrations in stream and river waters with increasing discharge (Figure 3a) can be attributed to the dilution effect, as widely observed in other river systems (e.g., Duvert et al., 2020; Roebuck et al., 2018; Reiman & Xu, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Bouchez et al (2010) indicated that OC petro was oxidized during transport in the Amazon River, at a rate of 0.25 Mt·C·yr −1 to the atmosphere. Ran et al (2018) measured the radiocarbon ages of degassed CO 2 during transit in the Wuding River basin and revealed that a significant fraction of old carbon was released to the atmosphere during fluvial transport (Figure 9). On geological timescales, the oxidation of OC petro during fluvial transport is a significant flux for the atmospheric CO 2 budget (Bouchez et al, 2010; Galy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%